Self-Tuning Speed Controller of the Induction Motor Drive - Kriauciunas, J.; Rinkeviciene, R.; Baskys, A. (Elektronika ir Elektrotechnika, 2014)
Induction motors are characterized by non-linear, complex and time-varying dynamics therefore conventional controllers cannot ensure speed step response specifications in all speed range. This paper presents hybrid fuzzy and proportional-integral-derivative (PID) controller to improve speed control of the induction motor. Proposed Fuzzy logic controller is used to tune each gain of PID controller separately. The simulation results are presented and discussed in the study. Simulink based model of induction motor drive is used for analysis of developed electromagnetic torque and speed response. Motor performance is thereby evaluated for speed control. DOI: http://dx.doi.org/10.5755/j01.eee.20.6.7262